Pengaruh Tindakan Supervisi, Kompleksitas Tugas dan Profesionalisme Auditor terhadap Kepuasan Kerja Auditor - Hasanati Hasanati; Akram Akram; M. Irwan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2017)
This study aims to examine and find the empirical evidence the effects of Supervisory Action, Task Complexity, and Auditor’s Profesionlism toward Auditor’s Job Satisfaction. The samples of this study are the Internal Control Officers (APIP) in Regional Inspectorate in Sumbawa Island, Nusa Tenggara Barat Province. Total sample are 81 which consists of 50 Auditor Officers (JFA) dan 31 Control Officers (P2UPD) whose as member in audit team, selected by using sampling technique of purposive sampling. The research results showed that Supervisory Action and Task Complexity have positive significant influence on Auditor’s Satisfaction.This study also find evidence that Auditors’ Professionalism able to effects Job Satisfaction negatively.